Estudio de la producción per-cápita de los residuos sólidos generados en cantón Zamora para la implementación de puntos de recolección de residuos segregados en el periodo 2021 -2022. - Rodríguez Pérez, Luis Fernando (2022)
Municipal solid waste is the waste from all human activities and its final destination is a sanitary landfill because of its uselessness, in order to avoid environmental contamination. Nowadays, the rapid growth of cities generates more waste, something that cities must face when designing efficient and cost-effective waste management plans. The present project is mainly focused on analyzing the current state of the integral management system of the Decentralized Autonomous Government of Zamora "GADMZA", focused on the social, cultural, economic and environmental problems to develop a proposal based on field studies, optimize waste management, determine the parameters of national and international environmental legislation, the proper management of waste in the collection management stage for optimization of human, technical and technological resources in the city of Zamora. The main objective was to study, quantify and characterize the production of solid waste per capita in the city of Zamora in order to determine a PPC of 0.64% kg/hab/day. Based on the results, it was concluded that the production of solid waste in the city of Zamora increased by 10% based on the study of the landfill in 2012. The proposal for the improvement of Integrated Solid Urban Waste Management is focused on environmental education, management and classification of solid waste generated by the population, through the location of ecological islands with resources from the Environmental Management Directorate of the GADMZA.